An Overview of Literary Developments in the Era of Pir Ali Mohammad Rashidi and Pir Hissamuddin Rashidi - Jamali, Sara (sourcecoder, 2023)
In the times of Rashidi brothers, there were very welcome developments in literary fields. Britishers brought better changes and introduced Sindhi as an official language replacing Persian, that was prevalent before their advent. They finally adopted an Arabic alphabet for Sindhi writing with an addition of 23 letters in it from other languages. These efforts were taken by Sir Bartel Farrer, and in this way Sindhi language was declared as an official language of Sindh. In such a way Sindhi literature began to flourish and flower. The British rulers not only introduced Sindhi Language in offices, but they also gave patronage to learning and literature through encouragement and appellations to intellectuals and scholars such as Shamsul Ulema “The Sun Amongst Scholars”. Many Sindhi periodicals and literary magazines started publishing in Sindhi by that time. In 1921, when Rashidi brothers were in their nacent ages, a tradition of “An All Sindh Literary Conference” was established and it took the start from Larkano, which kept on contributing till 1973. Larkano had to its credit almost 10 conferences, it hosted them outstandingly. Many prominent poets revolutionary writers are products of these literary sittings such as Kishan Chand Bewas, Comrade Haider Bux Jatoi, Allah Bux Abojho, Shaikh Ayaz, Khial Das Fani and Hari Dilgir etc they brought revolutionary changes in poetic thought and art and freed poetry from Persian larded language and ideas. After independence, Sindhi Language and Literature suffered a lot, right from the period of calamitous One Unit till 1973, when Sohini, Malir, Agtay Qadam, Pegham and other magazines were banned, 30 books were proscribed, and freedom of expression was gagged, but our writers and poets did not lose heart and continued to resist the ruthlessness with the power of the pen. Again in 1977, martial law was imposed, the Sindhi writers and poets faced flogs and physical tortures in the prisons. Pir Ali Mohammad Rashidi and Pir Hissamuddin Rashidi were also luminaries of Sindhi and urdu literature and their contributions in it carry much worth and value and their books mentioned herein betray literary scholarship, “Ho Dothy Ho Deenhn”, Uhe Deenhn Uhe Sheenhn and Makli Nama are worth repeat reading books.They are considered among accomplished and scholarly Urdu and Sindhi Writers of their times.